Audit market concentration and auditor's industry specialisation: an empirical evidence in Malaysia - Mohd Iskandar, Takiah; Maelah, Ruhanita; Aman, Aini (Sekolah Pengurusan, Universiti Utara Malaysia, 2000)
Industry specialisation refers to the concentration of auditors' work within specific industrie. Past studies show that industry specialisation exists in the US (e.g., Danos & Eichenseher, 1982; Eichenseher & Danos, 1981; Rhode, Whitsell, & Kelsey, 1974; Schiff & Fried, 1976; Zeff & Fossum, 1967) and Australia (e.g., Craswell Francis & Taylor, 1994; Craswell & Taylor, 1991). These studies recognised that industry specialisation is an important dimension to the audit market. It is argued that industry specialisation has positive impact on cost and product quality. This study extends previous studies by examining the practice among Big 6 and non Big 6 audit firms in Malaysian. In addition, the study also investigates features that characterise the clients. The results show that Big 6 audit firms acquire more than 60 percent of the audit service market share in almost all industries and their market share expands over time.